Mariano Ponce y Collantes dangal ng lahing Pilipino : aklat pang-alaala para sa sentenaryo ng kamatayan ni Mariano Ponce - Veneracion, Jaime B. (Jaime Balcos); Veneracion, Jaime B. (Jaime Balcos) (National Historical Commission of the Philippines, 2018)
Biography of Mariano Ponce y Collantes, a hero in Philippine press during the Spanish colonial; in commemoration of 100th death anniversary of Mariano Ponce y Collantes.